Web-based and traditional outsourcing - Sharma, Vivek; Sharma, Varun (Infosys press, 2012)
"The book elucidates various outsourcing aspects and tackles nagging questions: * Should Outsourcing be considered at all or not? If so, what functions are potential candidates? * What factors contribute to outsourcing success and why do some companies flounder? * What do successful companies that solve customer problems do differently? * How may the Web be tapped to open a whole new world of outsourcing online? * During economic slowdown, what outsourcing business strategies need to be applied? Offering counsel on whether or not a function should be in house or contracted/outsourced and further how it should be properly evaluated is considered a complex and debatable topic and often there seem too many variables that favor one over the other. The book provides deep insight into such aspects of the outsourcing industry, which is under great flux. Lowering costs, enhancing quality and development of life cycle have been at the core of IT - ITES space. Outsourcing is now considered a strategic tool in the arsenal with businesses reaping its benefits in a fiercely competitive global business environment. The book is concerned with various outsourcing facets and provides current exhaustive business relevant material about the industry. Managing outsourced projects involve continuous people - technology dynamics along with cross cultural and geographic challenges. The authors have elucidated in the book that the greatest business enablers are the concept, people and technology. Emerging trends and practices in the outsourcing industry have been dealt with including practical ideas to facilitate success in outsourcing initiatives"-- Provided by publisher